Art reaches within: aesthetic experience, the self and the default mode network - Vessel, Edward A.; Starr, G G.; Rubin, Nava (Frontiers in Neuroscience, 2013)
In a task of rating images of artworks in an fMRI scanner, regions in the medial prefrontal cortex that are known to be part of the default mode network (DMN) were positively activated on the highest-rated trials. This is surprising given the DMN's original characterization as the set of brain regions that show greater fMRI activity during rest periods than during performance of tasks requiring focus on external stimuli. But further research showed that DMN regions could be positively activated also in structured tasks, if those tasks involved self-referential thought or self-relevant information. How may our findings be understood in this context? Although our task had no explicit self-referential aspect and the stimuli had no a priori self-relevance to the observers, the experimental design we employed emphasized the personal aspects of aesthetic experience. Observers were told that we were interested in their individual tastes, and asked to base their ratings on how much each artwork "moved" them. Moreover, we used little-known artworks that covered a wide range of styles, which led to high individual variability: each artwork was rated highly by some observers and poorly by others. This means that rating-specific neural responses cannot be attributed to the features of any particular artworks, but rather to the aesthetic experience itself. The DMN activity therefore suggests that certain artworks, albeit unfamiliar, may be so well-matched to an individual’s unique makeup that they obtain access to the neural substrates concerned with the self – access which other external stimuli normally do not get. This mediates a sense of being “moved”, or “touched from within.” This account is consistent with the modern notion that individuals’ taste in art is linked with their sense of identity, and suggests that DMN activity may serve to signal “self-relevance” in a broader sense than has been thought so far.